2021
DOI: 10.1021/acs.est.0c05851
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Nitrogen Oxides and Fine Particulate Matter near Major Highways in the United States Using the National Near-Road Monitoring Network

Abstract: As part of the United States Environmental Protection Agency’s 2010 Nitrogen Dioxide (NO2) National Ambient Air Quality Standards (NAAQS) review, a national network of near-road sites was established to characterize pollutant behavior, interaction, and dispersion in the ambient near-road environment. Using spatial interpolation to estimate the near-road concentration increments of NO2 and particulate matter with an aerodynamic diameter of 2.5 μm and less (PM2.5) relative to nearby non-near-road monitors, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Near roadways, nitric oxide concentrations can reach concentrations well in excess of 10 ppb. 44 Nitric oxide is also a chemical messenger in the human body. It is normally found in breath at concentrations near 200 ppb, and NO deficiencies have been linked to a variety of diseases.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near roadways, nitric oxide concentrations can reach concentrations well in excess of 10 ppb. 44 Nitric oxide is also a chemical messenger in the human body. It is normally found in breath at concentrations near 200 ppb, and NO deficiencies have been linked to a variety of diseases.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Diesel vehicles in particular generate significant amounts of nitric oxide. Near roadways, nitric oxide concentrations can reach concentrations well in excess of 10 ppb . Nitric oxide is also a chemical messenger in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Communities Near Roads Recent modeling and monitoring analysis have shown that near-road concentration of PM2.5 could be higher than the nearby non-near road or background monitors by about 1 µg/m 3 (DeWinter et al 2018;Craig et al 2020;Gantt, Owen, and Watkins 2021). Some recent studies have shown that electrification will benefit environmentally disadvantaged communities.…”
Section: A6 Environmental Justice Implicationsmentioning
confidence: 99%
“…The Moderate Resolution Imaging Spectroradiometer (MODIS) onboard the Aqua and Terra satellites measures AOD and has nominal overpass times on a sun-synchronous near-polar orbit of 10:30 a.m. (descending) and 1:30 p.m. (ascending) local time, 25,26 which does not correspond to peak concentrations. 27,28 During six weeks of direct surface measurements during the Southern Oxidant and Aerosol Study (SOAS), 29 hourly ALW mass concentrations and particle hygroscopicity peak at approximately 8 a.m. Throughout the CONUS, peak values in ALW and nitrate mass are perceived to occur on cloudy days 22,30 when remotely sensed AOD is least reliable.…”
Section: Introductionmentioning
confidence: 99%